Elites : a general model - Milner, Murray (Cambridge, UK ; Malden, MA : Polity Press, 2015)
At a time when significant social status, economic resources, and political opportunities seem to become ever more unequally distributed and only available to a few, this book represents the first systematic effort in recent years to develop a sociological model of elites and non-elites. In outlining a new typology of economic, political, and cultural elites, as well as drawing attention to the important role of non-elites, this accessibly written book provides novel insights into the structure of historical and contemporary societies. Milner identifies the sources and structures of economic, political, and cultural power, and investigates patterns of cooperation and conflict between and within elite groups. Analyzing politicians and propagandists, landowners and capitalists, national heroes and celebrities, ordinary folks and outcasts, the book applies its model to three distinctly different societies - ancient India, Classical Athens, and the contemporary United States - highlighting important structural commonalities across these otherwise very dissimilar societies. -- from back cover.
Introduction -- The general model -- Traditional India : the Varna scheme -- Athens in the classical period -- The U.S. 1980-2008 : economics and politics -- The U.S. 1980-2008 : other actors -- The 2007-2009 financial crisis -- Conclusions.
Includes bibliographical references (pages 149-198) and index.
Keywords: Elite (Social sciences); Power (Social sciences); Elite (Social sciences) -- United States; Power (Social sciences) -- United States; Elite (Social sciences) -- India; Power (Social sciences) -- India